Suicide and the Gothic - Hughes, William, 1964-; Smith, Andrew, 1964-; Manchester University Press (Manchester, UK : Manchester University Press, 2019)
'Suicide and the Gothic is the first protracted study of how the act of self-destruction recurs and functions within one of the most enduring and popular forms of fiction. Comprising eleven original essays and an authoritative introduction, this collection explores how the act of suicide has been portrayed, interrogated and pathologised from the eighteenth century to the present. The featured fictions embrace both canonical and the less-studied texts and examine the crisis of suicide - a crisis that has personal, familial, religious, legal and medical implications - in European, American and Asian contexts. Featuring detailed interventions into the understanding of texts as temporally distant as Thomas Percy's Reliques and Patricia Highsmith's crime fictions, and movements as diverse as Wertherism, Romanticism and fin-de-siècle decadence, Suicide and the Gothic provides a comprehensive and compelling overview of this recurrent crisis in fiction and culture' --Publisher.
Introduction: 'The Most Gothic of Destructive Acts: Suicide in Generic Context' / William Hughes and Andrew Smith -- Chapter 1: 'Scottish Revenants: Thomas Percy, Ballad Editing and the fatality of Scotland' / Frank Ferguson (Ulster University) and Danni Glover (Ulster University) -- Chapter 2: 'Suicide as Justice? The Self-Destroying Gothic Villain' / Bridget M. Marshall (University of Massachusetts) -- Chapter 3: '"The supposed incipiency of mental disease": Guilt, Regret and Suicide in Three Ghost Stories by J. Sheridan Le Fanu' / William Hughes (Bath Spa University) -- Chapter 4: 'Aping the Gentleman: Self-murder and the Gentleman's Code in Hogg's Confessions of a Justified Sinner and Stevenson's Strange Case of Dr Jekyll and Mr Hyde' / Alison Younger (University of Sunderland) -- Chapter 5: '"The body of a self-destroyer": suicide and the self in the fin de siècle Gothic' / Andrew Smith (University of Sheffield) -- Chapter 6: '"To be mistress of her own fate": Suicide as Control and Contagion in the Works of Richard Marsh' / Graeme Pedlingham (University of Sussex) -- Chapter 7: 'Gothic Influences: Darkness and Suicide in the Patricia Highsmith and Ruth Rendell' / Fiona Peters (Bath Spa University) -- Chapter 8: 'The Tragedy of Life: The Appeal of (Mass) Suicide in Thomas Ligotti's Nihilistic Gothic' / Xavier Aldana Reyes (Manchester Metropolitan University) -- Chapter 9: 'Silencing the Ghosts: Problematic Reclamation of the Ghosts of Suicide in David Bradley's The Chaneysville Incident and Toni Morrison's Beloved' / Emma Wilde (Nottingham University) -- Chapter 10: 'Vampire Suicide' -- Jeffrey Andrew Weinstock (Central Michigan University) -- Chapter 11: 'Eaten Back to Life: Being-Towards-Death from Beyond the Grave; or, Cannibal Consumption as (Anti) Suicide in Contemporary Zombie Literature' / Stephen Curtis (Lancaster University) -- Chapter 12: 'Lost in the Land of the Dying Sun: Gothicising Attitudes to Suicide in Japanese Literature and Popular Culture' / Katarzyna Ancuta (Assumption University, Bangkok) -- Chapter 13: '"I will abandon this body and take to the air": the suicide at the heart of Dear Esther' / Dawn Stobbart (Lancaster University).
Made available via: manchesterhive.
In English.
Print version record
JSTOR
Keywords: Gothic fiction (Literary genre), English -- History and criticism; Suicide in literature; Suicide dans la littérature.; Literature and literary studies; LITERARY CRITICISM -- General; LITERARY CRITICISM / General; Suicide in literature; Gothic fiction (Literary genre), English; Gothic; Romanticism; crime fiction; eighteenth century; fin de siècle.; literature; nineteenth century; suicide; twentieth century; Electronic books; Criticism, interpretation, etc